2004
DOI: 10.1111/j.1365-277x.2004.00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal – neonatal folate and vitamin B12 serum concentrations in Greeks and in Albanian immigrants

Abstract: (a) Folate serum concentrations in Greek and Albanian mothers and in their neonates were similar, (b) vitamin B(12) serum concentrations, evaluated for first time in these ethnic groups, were significantly low in Albanians, both in mothers and newborns, (c) the low protein and especially the reduced animal protein intake from the Albanian mothers, possibly due to their low socio-economic status, may be responsible for their decreased vitamin B(12) serum concentrations and (d) vitamin B(12) supplementation alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
3
19
2
4
Order By: Relevance
“…It is interesting that studies concerning Albanian immigrants showed either directly or indirectly low meat consumption or low protein and micronutrients intake. 19,20 It is likely, even though our study did not definitely show it, that there may be a correlation of the occurrence of goiter with the socio-economic level of the patients. It could for instance be hypothesised that patients who can afford to consume meat more frequently are those who are economically better-off than those that do not have this privilege.…”
Section: Discussioncontrasting
confidence: 38%
“…It is interesting that studies concerning Albanian immigrants showed either directly or indirectly low meat consumption or low protein and micronutrients intake. 19,20 It is likely, even though our study did not definitely show it, that there may be a correlation of the occurrence of goiter with the socio-economic level of the patients. It could for instance be hypothesised that patients who can afford to consume meat more frequently are those who are economically better-off than those that do not have this privilege.…”
Section: Discussioncontrasting
confidence: 38%
“…With respect to folate, mean neonatal plasma concentrations of about 25 nmol/l have been described (Minet et al, 2000;Guerra-Shinohara et al, 2002;Refsum et al, 2004;Schulpis et al, 2004;Couto et al, 2007), which is comparable with our results. These relatively high plasma folate concentrations in newborns compared with adults might explain the loss of correlation with tHcy concentrations in this age category.…”
Section: Discussionsupporting
confidence: 82%
“…However, we also found high rates of vitamin B-12 insufficiency in 4 studies from Turkey and in 1 study from Greece (28,52,65,77,93). The "Mediterranean diet" contains plenty of fruit, vegetables, and pulses compared with meat (118), which may in part explain this observation because stricter adherence to the diet during pregnancy exacerbated vitamin B-12 deficiency (52).…”
Section: B-12 Insufficiency In Pregnancy and Birth Weightmentioning
confidence: 80%
“…An additional striking finding was the pooled insufficiency rate of 65% (I 2 = 95%) ( Figure 4) (28,52,65,77,93) from the 5 studies in the Eastern Mediterranean region. On the contrary, insufficiency rates of ,8% were found in 2 studies conducted in Thailand and Sudan, where the authors attributed the low rates of insufficiency to the consumption of fish and animal/fermented products, respectively (although details of dietary intake were not provided) (49,50).…”
Section: Prevalence Of Vitamin B-12 Insufficiency In Pregnancymentioning
confidence: 98%
See 1 more Smart Citation